2015
DOI: 10.3136/fstr.21.549
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cheese Maturation with the Fluorescence Fingerprint

Abstract: The objective of this research was to develop a method using the fluorescence fingerprint (FF) to measure cheese

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The peak at the excitation wavelength of 300 nm and the emission wavelength of 680 nm represents the second-order light of the excitation wavelength of 300 nm and the emission wavelength of 335 nm, which appears owing to the light dispersion mechanism of the monochrometer (i.e., the same mechanism that creates the second-order scattering light). In the FF data, similar peaks were detected to those in Kokawa et al (2015); thus, we confirmed that a non-contact FF could be obtained for cheese using an optical fiber. Table 1 shows the age, composition and pH of 10 sample cheeses.…”
Section: Pls Model For Prediction Of Cheese Body Measurementsupporting
confidence: 84%
See 2 more Smart Citations
“…The peak at the excitation wavelength of 300 nm and the emission wavelength of 680 nm represents the second-order light of the excitation wavelength of 300 nm and the emission wavelength of 335 nm, which appears owing to the light dispersion mechanism of the monochrometer (i.e., the same mechanism that creates the second-order scattering light). In the FF data, similar peaks were detected to those in Kokawa et al (2015); thus, we confirmed that a non-contact FF could be obtained for cheese using an optical fiber. Table 1 shows the age, composition and pH of 10 sample cheeses.…”
Section: Pls Model For Prediction Of Cheese Body Measurementsupporting
confidence: 84%
“…These model system studies demonstrated that oxidized lipid and Maillard reaction products of milk and dairy products could be monitored via their fluorescence in the 13 range near the excitation wavelength of nm and the emission wavelength of nm. In addition, Kokawa et al (2015) selected peaks at an excitation wavelength of 345 nm and emission wavelength of 400 nm as the wavelength values with a large contribution to the PLS regression model in the FF of cheese maturation indices, which suggested that oxidized lipids and Maillard reaction products are present in Cheddar cheese. These are thus considered to be the same substances as measured in the present study, as we also focused on these wavelengths based on the VIP values in this study.…”
Section: Vip and Sr Scores Of The Plsr Model Plotted Using Ff Contourmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein carbonyls are formed only in the presence of reducing sugars and may act as early precursors for the later production of AGEs-fluorophores [16]. These compounds have been used as a parameter of ripening in cheeses [4,27,28] and their formation was accompanied by the loss of galactose in Manchego cheese [29].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the FF technique over conventional fluorescence spectroscopy is that it includes the signals of many fluorescent constituents existing in the sample. Many studies using the FF technique to evaluate various food stuffs, such as olive oil (Guimet et al 2006), beer (Sikorska et al 2008), cheese (M. Kokawa et al 2015), soymilk (Mito Kokawa et al 2017, and apples (Trivittayasil et al 2018), have been reported. Trivittayasil et al (2017) reported that a model for estimating the active oxygen-scavenging ability of peach extract was constructed from the fluorescence patterns of epicatechin and procyanidin (Trivittayasil et al 2017).…”
Section: Introductionmentioning
confidence: 99%